Satisfaction of Cuban Graduates from the Medical Major with the received training. Academic Year 2015 2016, Cienfuegos - Mabel Rocha Vázquez; Mirtha Amarilis Hernández López; María Isabel Mantecón Ledo; Dunia Chávez Amaro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: Educative evaluation is the systematic process of obtaining information and using it to offer judgments which will allow making decisions and improving the teaching educative process. University Education requires permanent evaluation to guaranty quality. Objectives: To determine the satisfaction of Cuban graduates from the Medical Major regarding the received training. Methods: A cross section descriptive study was carried out at the Cienfuegos Medical University, from July to November 2016. It was applied a survey of the Higher Education National Crediting Committee to a sample of 62 Cuban graduates from the Medical Major in the academic year 2015-2016. Results: More than 80 % of the surveyed showed their satisfaction regarding the contribution of the Major to the promotion and consolidation of the personal qualities so as the training received for the professional performance and the teaching staff performance. It was observed dissatisfactions in relation to the acquisition of the English language, the Information and Communication Technologies, the assistance of advisors and tutors to develop research. There was also dissatisfactions in with respects to the rehabilitation and treatment competences. Conclusion: There are dissatisfactions in the Medical graduates, more evident in the development of general and specific competences related to the treatment, so as in their raining to perform administrative task which are necessary in their professional performance.